Assessing Needs for Quality Improvement: A Study of Nature-Based Education Principles (Sekolah Alam Way) at Saga Lifeschool, Indonesia - Robianti, Febi; Raufu, Mufutau; Sasongko, Marsahid; Sikirat Abolanle Busari-Raufu; Raufu, Jemilat; Yamani, Khalila (Indonesian Journal Publisher, 2024)
Nature-based education offers a transformative approach to sustainable education by integrating natural environments and sustainability principles into active learning experiences. In Indonesia, Saga Lifeschool, along with over 200 nature-based schools under Jaringan Sekolah Alam Nusantara (JSAN), exemplifies this model through its